(untitled) (Confluenţe Bibliologice, 2023)
The article presents information about the activity of the bishops of the diocesan of Ismail - White Fortress ,Policarp Maruşca and Antim Nica oriented towards the enlightenment of the people by editing the publication , Cuvântul adevărului” and the Bulletin of the Ismail White Fortress Episcopate , publications that cultivated love for the homeland and nation.